2005
DOI: 10.1080/01904160500310997
|View full text |Cite
|
Sign up to set email alerts
|

Control of Fusarium Wilt of Cucumber Seedlings by Inoculation with an Arbuscular Mycorrhical Fungus

Abstract: A glasshouse pot experiment was conducted to investigate the impact of inoculation of cucumber at the germination stage with Glomus etunicatum BEG168 on plant yield and incidence of Fusarium oxysporum f.sp. cucumerinum inoculated 28 days after the start of the experiment. Inoculation with the AM fungus decreased both disease incidence and disease index. Mycorrhizal inoculation also increased P concentrations in the cucumber seedlings. The mycorrhizal seedlings had higher concentrations of proline and polypheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 32 publications
1
26
0
1
Order By: Relevance
“…Mathur and Vyas [28] showed a considerable increase in PPO activity in AM fungus (Glomus fasciculatum) inoculated Ziziphus xylopyrus. Hao et al [29] also suggested an increase in PPO activity with mycorrhizal inoculation as a defense mechanism of plants.…”
Section: Mycorrhizal Colonizationmentioning
confidence: 95%
“…Mathur and Vyas [28] showed a considerable increase in PPO activity in AM fungus (Glomus fasciculatum) inoculated Ziziphus xylopyrus. Hao et al [29] also suggested an increase in PPO activity with mycorrhizal inoculation as a defense mechanism of plants.…”
Section: Mycorrhizal Colonizationmentioning
confidence: 95%
“…The evaluation of Fusarium wilt disease was conducted three weeks after inoculation by determining the percentage of disease severity according to Hao et al (2005). The following 0 to 5 scales was used: 0 -without symptoms 1 -leaf chlorosisand plant wilt less than 25% 2 -leaf chlorosisand plant wilt from 25 to 50% 3 -leaf chlorosisand plant wilt from 51 to 75% 4 -leaf chlorosisand plant wilt from 76 to 100% 5 -dead or fully destroyed plant where: n i = the number of the samples with the same olisease scale; v i = the olisease scale for every sample; N = total samples in each replications; V = maximum olisease scale.…”
Section: Evaluation Methods Of Fusarium Wiltmentioning
confidence: 99%
“…Flowers are open for a single day and are visited by a variety of generalist pollinators including honey bees (Apis mellifera, Apidae; see Plate 1), bumble bees (Bombus spp., Apidae), a variety of solitary bees (e.g., Halictidae, Andrenidae), butterflies, and hover-flies (Syrphidae). Cucumis sativus is commonly colonized by AMF, and the symbioses have been shown to affect flowering, fruit production, photosynthesis rates, and disease resistance (Trimble and Knowles 1995, Valentine et al 2001, Hao et al 2005.…”
Section: Study Systemmentioning
confidence: 99%